Interactive Computer Play as “Motor Therapy” for Individuals With Cerebral Palsy. - Fehlings, Darcy; Switzer, Lauren; Findlay, Briar; Knights, Shannon (Seminars in Pediatric Neurology, 2013)
The aim of the study was to evaluate the quality of evidence for interactive computer play (ICP) to improve motor performance (including motor control, strength, or cardiovascular [CVS] fitness) in individuals with cerebral palsy. A computer-assisted literature search was completed, focusing on ICP as a therapeutic modality to improve motor outcomes in individuals of all ages with cerebral palsy with a specific focus on upper and lower extremity motor outcomes and promotion of CVS fitness. Articles were classified according to American Academy of Neurology guidelines and recommendation classifications were given based on the levels of evidence. Seventeen articles underwent full-text review including 6 on upper extremity motor function, 5 on lower extremity motor function, 1 on CVS fitness, and 5 on studies with a combination of upper or lower extremity or CVS fitness focus or both. Overall, there was level B (probable) evidence for ICP interventions to improve lower extremity motor control or function. However, there was inadequate evidence (level U) for ICP interventions improving upper limb motor control or function or CVS fitness. Although promising trends are apparent, the strongest level of evidence exists for the use of ICP to improve gross motor outcomes. Additional evidence is warranted especially when evaluating the effect of ICP on upper limb motor outcomes and CVS fitness.